2020
DOI: 10.1111/nyas.14473
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic treatment of GERD: Where we are now, and where are we going?

Abstract: The introduction of acid inhibition in clinical practice has revolutionized the management of acid-related diseases, leading to the virtual abolition of elective surgery for ulcer disease and relegating antireflux surgery to patients with gastroesophageal reflux disease (GERD) not adequately managed by medical therapy. Proton pump inhibitors (PPIs) are the antisecretory drugs of choice for the treatment of reflux disease. However, these drugs still leave some unmet clinical needs in GERD. PPI-refractoriness is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 189 publications
(327 reference statements)
0
21
0
10
Order By: Relevance
“…In recent years, another mechanism, such as the reduction of defensive properties of esophageal mucosa has been advocated in the pathogenesis of GERD. 16 There are many studies showing that the mucosal resistance of the esophagus is impaired in most patients with GERD, particularly in those with non-erosive reflux disease (NERD), who do not present mucosal lesions at endoscopy. 16,17 Indeed, the presence of dilated intercellular spaces (DIS) is common in patients with true NERD and reflux hypersensitivity (RH) because of the presence of an impaired mucosal barrier.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, another mechanism, such as the reduction of defensive properties of esophageal mucosa has been advocated in the pathogenesis of GERD. 16 There are many studies showing that the mucosal resistance of the esophagus is impaired in most patients with GERD, particularly in those with non-erosive reflux disease (NERD), who do not present mucosal lesions at endoscopy. 16,17 Indeed, the presence of dilated intercellular spaces (DIS) is common in patients with true NERD and reflux hypersensitivity (RH) because of the presence of an impaired mucosal barrier.…”
Section: Figurementioning
confidence: 99%
“…16 There are many studies showing that the mucosal resistance of the esophagus is impaired in most patients with GERD, particularly in those with non-erosive reflux disease (NERD), who do not present mucosal lesions at endoscopy. 16,17 Indeed, the presence of dilated intercellular spaces (DIS) is common in patients with true NERD and reflux hypersensitivity (RH) because of the presence of an impaired mucosal barrier. 18 In patients with NERD it has been shown that microscopic esophagitis, including DIS, is significantly lower in controls (15%) and in patients with functional heartburn (FH) (13%) than in patients with RH (65%) and in those with excess of acid (77%).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…PPIs have been widely used for decades, but the number of recent publications questioning their safety has increased dramatically, causing considerable patient anxiety. Evidence has shown that they are risk-free drugs with relatively rare adverse effects and very low mortality (61,62) . There are certainly cases where there is a risk of vascular complications, regardless of the use of PPIs, such as in elderly patients with diabetes, hypertension, and history of strokes, who often require aspirin for prophylaxis of cardio-cerebrovascular events (63) .…”
Section: Figurementioning
confidence: 99%
“…They include inhibition of peptic digestion, mucosal protection through mucus and bicarbonate production, and stimulation of tissue growth and repair. 46 In the past, sucralfate has been extensively used in adults with GERD, 47 but with advent of PPIs, it was relegated to other gastrointestinal (GI) conditions. The available data are inadequate to determine the safety or efficacy of sucralfate in the treatment of GERD in children, particularly the risk of aluminum toxicity with long-term use.…”
Section: Introductionmentioning
confidence: 99%